SPIRITUAL AND MORAL EDUCATION OF THE FUTURE OFFICERS OF THE PENITENTIARY SYSTEM IN THE PROCESS OF THEIR PROFESSIONAL TRAINING - Elena A. Timofeeva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This article analyzes the current requirements for quality and level of professional training of future officers-graduates of law high schools of the Federal Penitentiary Service of Russia. Tracing the genesis of the concept "officer", the author, referring to the experience of spiritual and moral education of cadets in Samara Law Institute of FPS of Russia, shows how is in the Institute, based on a deep respect for the traditions of education of Russian officer, associated with Orthodoxy, can develop and strengthen cooperation with the Russian Orthodox Church. The author attempts to trace the main paths of spiritual and moral education of the future officers in the process of high school courses. An analysis of the educational program "Spiritual and moral education of Russian officers", seminars, training courses and events, the author convincingly demonstrates how the process of spiritual and moral education has become one of the most important directions of the departmental Institute.